2013
DOI: 10.1007/s11914-013-0154-3
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis and Cancer

Abstract: Cancer is a major risk factor for bone loss and fractures. This is due both to direct effects of cancer cells on the skeleton and to deleterious effects of cancer-specific therapies on bone cells. Marked improvements in survival for many cancers mean that strategies to limit bone loss and reduce fracture risk must be incorporated into the care plans for nearly all patients with cancer. The vast majority of effort thus far has focused on bone loss in patients with breast and prostate cancers, with comparatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 75 publications
(72 reference statements)
0
48
1
3
Order By: Relevance
“…Falls among older adults with a cancer diagnosis are of added concern because cancer itself and certain cancer treatments can compromise bone health and physical function which, in turn, increase the risk for falls and fractures [8]. Several studies of community-dwelling older adults have found significant differences in fall rates between elderly persons with and without a cancer diagnosis, with one study reporting 26.4 vs 21.9 % (odds ratio, OR=1.17, p ≤0.001) [9] and another reporting 33 vs 26 % (OR=1.16, p =0.03) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Falls among older adults with a cancer diagnosis are of added concern because cancer itself and certain cancer treatments can compromise bone health and physical function which, in turn, increase the risk for falls and fractures [8]. Several studies of community-dwelling older adults have found significant differences in fall rates between elderly persons with and without a cancer diagnosis, with one study reporting 26.4 vs 21.9 % (odds ratio, OR=1.17, p ≤0.001) [9] and another reporting 33 vs 26 % (OR=1.16, p =0.03) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis and osteopenia are a common sequela for patients with bone metastases. This is due to the direct effects of cancer cells on the skeleton and to deleterious effects of cancer‐specific therapies on bone cells [37]. In a case controlled analysis of 174 hormone‐naive men with advanced prostate cancer, 42% were osteoporotic and 37% were osteopenic at diagnosis compared with a 27% incidence of osteoporosis amongst peer‐matched controls ( P = .02) [38].…”
Section: Section Two: Considerations For Exercise Prescriptionmentioning
confidence: 99%
“…The skeleton is a dynamic tissue whose constant remodeling depends upon the balance of osteoclast-mediated bone resorption and osteoblast-mediated bone formation. Various diseases have been related to an osteoblast-osteoclast imbalance, including osteoporosis, rheumatoid arthritis, gum disease, and metastatic bone cancer [14,15].…”
Section: Skeletal Homeostasismentioning
confidence: 99%